The Role of Guided Questions in Enhancing Student’s English Writing Ability - Mu'min; Reskiawan, Bimas; Astiantih, Susi (LifeSciFi, 2025)
Many students encounter challenges in organizing ideas, developing content, and maintaining coherence in descriptive writing tasks. In response to this issue, guided questions were introduced as a structured instructional approach to help students think critically and write more effectively. The purpose of this research was to analyze the differences in students’ writing performance before and after the implementation of the guided questions strategy and to compare the results with those of students who were taught using traditional methods. The research used a quasi-experimental design involving 70 students, divided into control and experimental groups. Both groups completed pre-tests and post-tests focused on descriptive text writing. Data were analyzed using descriptive statistics to observe patterns of improvement. The results showed that students in the experimental group experienced greater improvement in their writing scores and moved into higher performance categories compared to the control group. The results have implications for educators that guided questions offer practical and adaptable approach to support students in developing their writing skill. These findings suggest that the guided questions strategy can enhance students’ ability to generate and organize ideas in writing. Therefore, this strategy is recommended as an effective method for improving writing instruction in similar educational contexts.